Designing Learning Game for Human Digestive System Based on Motion Sensors - Gregorius Alvin Raditya Santoso; Albertus Dwi Yoga Widiantoro; Ridwan Sanjaya (Journal of Business and Technology, 2021)
Nowaday rapid development of communication and information technology also influences the sector of education. The main activity in the education process is learning. Learning is a process of interaction between students and their environment, leading to better behavior changes [1].One of the learning subjects that students must learn is science. But Indonesian student’s scientific literacy is still low [2]. Students still consider science subjects difficult and boring [3]. One learning material that is classified difficult is the human digestive system [4]. Therefore a solution is needed to make interesting learning one of them by using learning media.Learning media that can be used for the solution is game based on motion sensors. By using games, students will be happy to accept the learning process. Based on a survey conducted on 30 respondents of junior high school students in the Semarang, it turns out that the game used as a human digestive system learning media is able to provide positive results. Through this game students can understand the digestive system material and more enthusiastic in learning.